2023
DOI: 10.3389/fmech.2023.1108180
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy simulation of a 15 GW wind farm: Flow effects, energy budgets and comparison with wake models

Abstract: Planned offshore wind farm clusters have a rated capacity of more than 10 GW. The layout optimization and yield estimation of wind farms is often performed with computationally inexpensive, analytical wake models. As recent research results show, the flow physics in large (multi-gigawatt) offshore wind farms are more complex than in small (sub-gigawatt) wind farms. Since analytical wake models are tuned with data of existing, sub-gigawatt wind farms they might not produce accurate results for large wind farm c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The studies mentioned above showed that the presence of AGWs have two main implications, namely an adverse pressure gradient upwind the wind farm, which is responsible for global blockage, and a favorable pressure gradient inside the wind farm that is beneficial for wake recovery. Moreover, Centurelli et al (2021) and Maas (2023) showed that LES results strongly differ from reduced-order wake models when thermal stratification is considered. To assess the impact of inversion height, strength and lapse rate on wind farm blockage, Lanzilao and Meyers (2023) conducted an LES parametric study, concluding that the overall effect of AGWs on wind farm operation is either beneficial or detrimental depending on the specific structure of the potential temperature profile.…”
Section: Introductionmentioning
confidence: 99%
“…The studies mentioned above showed that the presence of AGWs have two main implications, namely an adverse pressure gradient upwind the wind farm, which is responsible for global blockage, and a favorable pressure gradient inside the wind farm that is beneficial for wake recovery. Moreover, Centurelli et al (2021) and Maas (2023) showed that LES results strongly differ from reduced-order wake models when thermal stratification is considered. To assess the impact of inversion height, strength and lapse rate on wind farm blockage, Lanzilao and Meyers (2023) conducted an LES parametric study, concluding that the overall effect of AGWs on wind farm operation is either beneficial or detrimental depending on the specific structure of the potential temperature profile.…”
Section: Introductionmentioning
confidence: 99%